Investigation of BaFe12O19 hexaferrites manufactured by various synthesis methods using a developed pulsed magnetometer - Wagner, Dmitriy V.; Kareva, Katerina V.; Zhuravlev, Victor A.; Dotsenko, Olga A.; Minin, Roman V. (Inventions)
The manufacture and study of the properties of magnetic materials requires the development of new automated devices for measuring their magnetic properties. To obtain nanosized materials with a pure phase, it is necessary to modernize former methods and develop new methods for synthesizing materials. As part of this study, a pulse magnetometer was made to study magnetic hysteresis loops. An exceptional feature of this device is the ability to conduct studies of the full cycle of the hysteresis loop using pulsed magnetic fields. M-type BaFe12O19 hexagonal ferrites were synthesized by standard ceramic, mechanochemical, and sol–gel methods. The structural, phase, and magnetic characteristics of the barium hexaferrites were studied. Methods for the synthesis of BaFe12O19 hexagonal ferrites were estimated and compared. Their structural and magnetic properties essentially depend on the method of synthesis. The mechanochemical technology makes it possible to obtain materials without impurity phases through the use of hydrated reagents in the synthesis. The use of sol–gel technology allows the synthesis to be carried out at much lower temperatures.